(untitled) (Sains Humanika, 2023)
A survey was conducted to identify the professionalism traits among education students, namely Manner Towards Teacher (AB), Appearance (PN), Oral Communication (KL), Respect (HM), Respect for Time (MM), Digital Communication (KD), Integrity (IG), Gratitude (BS), and Group Work (KK). The items were constructed based on operational definitions from the literature and adapted based on the current context. The first administration (pre) of the Educational Student Professionalism Trait Questionnaire (STPMP) was in the second week, while the second administration (post) was in the thirteenth week of the study session 2021/2022 semester 1. The administrations were done through the Google Form application on 126 students taking Teacher Professionalism Course. Both data sets were analyzed to identify professionalism traits (pre and post), professionalism traits based on gender, the relationship between dimensions, and dominant dimensions that are predictors of professionalism traits. STPMP had undergone a consistency verification process (N = 42) where the Cronbach’s Alpha (r) reliability index is at (.95). The findings of the study showed that the mean score for the professionalism traits of the education students is at a moderately high level, while the mean score for the professionalism traits of male students is higher than female students. Next, (BS) is the highest dimension, while (MM) is the lowest dimension. There is also a significant effect on the professionalism of the student (p <0.05); four dominant dimensions are KK (.185), MM (.158), BS (.149), and AB (.139). IG is the dimension least influencing the professionalism traits of educational students.